Desenvolvimento de genossensor para diagnóstico de neuroblastoma - Silva, Thalles Douglas Souza e (2014)
A novel electrochemical genosensor with modified graphite with poly(4-aminophenol) has been constructed for detection of neuroblastoma, a malignant tumor originating from embryonic precursor cells of the sympathetic nervous system and associated with the amplification MYCN oncogene. The produced genosensor exhibited distinct electric and morphological properties using rhodamine b, specie able to bind with DNA duplex, as indicator of the hybridization process. The detection limit was evaluated to be 0.47 umol.L-1 (N=3) and showed very high selectivity for the complementary DNA using serum sample. This DNA sensing platform was successfully applied to detect the MYCN, an important biomarker for neuroblastoma